HUBUNGAN KELELAHAN KERJA DENGAN KEJADIAN KECELAKAAN KERJA PADA PEKERJA GALANGAN KAPAL - Aulia ,; Aladin ,; Mariaman Tjendera (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2018)
Fatigue and workplace accidents are part of occupational health and safety science. One form of the accident was the explosion of a ship at one of the shipyard companies in Batam. This accident can occur due to human factors such as fatigue. Fatigue causes unsafe work behavior that causes workplace accidents. Fatigue is easier for shipyard workers because of the heavier workload. So the researchers wanted to find a relationship between fatigue and the incidence of workplace accidents at PT. Bandar Abadi Shipyard. The research method is observational analytic with cross sectional approach conducted at PT. Bandar Abadi Shipyard Batam. The sampling technique was simple random sampling with a population of 416 workers and obtained the results of 200 workers determined by inclusion and exclusion criteria. The results of the study were analyzed and tested by Chi-square test. The results showed that there were 51 (58.6%) workers who were not fatigued and did not work accidents, 36 (41.4%) workers who were not fatigue and workplace accidents. Whereas 38 (33.6%) workers and workers who were exhausted and did not work accidents were exhausted and workplace accidents were 75 (66.4%) workers. The Chi-Square analysis results obtained a significance value of p = 0,000. This number is significant because the p value is smaller than 0.05. So it can be concluded that there is a significant relationship between fatigue and the incidence of workplace accidents. The relative value of risk in this study was 2,796. With this value, it can be interpreted that workers who experience fatigue are at risk of 2,796 or almost 3 times to experience workplace accidents compared to workers who do not experience fatigue.